IMPLICATION OF BOARD COMPOSITION ON FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA (UNIZIK Journal of Marketing, 2025)
The paper titled, implications of board composition on financial performance of listed deposit money banks in Nigeria, aims to examine how board structures influence the effectiveness of corporate governance and overall performance of Nigeria’s banking sector. There were two research questions and two hypotheses generated to examine the situation. The research design is ex post factor design, the population of the study is all the deposit money banks listed on Nigeria exchange group out of which 10 were taken as sample based of purposive sampling technique informed by availability of data for analysis and date of listing which must be before year end 31.12.2019. Secondary data was collected from secondary source through the annual report and account of the banks and was analyzed through the support of STATA 14 versions.  Descriptive statistics, correlation matrix and OLS multiple regression model were adopted for the study. Breusch and pagan lagrangian multiplier test for random effect was conducted. The findings of the study reveal that board size has positive and significant impact on Tobin’s Q, gender diversity has positive and significant impact on Tobin’s Q, while, board independent had a negative and insignificant influence on the Tobin’s Q. Similarly, firm size was found to have a negative and insignificant impact on Tobin’s Q of the study banks.
Keywords: Implication, Board Composition, Financial Performance, Listing of DMBs, Nigeria